Extratos de canola no controle de botrytis cinerea in vitro e do mofo cinzento em pós-colheita de morangos - Cuzzi, Claucia (2013)
The gray mold is caused by the fungus Botrytis cinerea (Pers.: Fr.), causer of great economic losses in various cultures. This pathogen is difficult to control, due to the wide range of hosts, its saprophytic activity and by forming structures of resistance (esclerodios). One of the ways to control this pathogen is the use of chemical products, however, mainly in post-harvest fruit, tolerance by chemical residues in foods is increasingly less desirable from an ecological and public health point of view. The alternative treatments, such as the use of plant extracts, are being probed in phytopathology, to reduce the use of synthetic fungicides. The canola (Brassica napus) is a plant that has biocidal compounds, with potential to control pests and diseases. This study aimed to evaluate the effect of different extracts of canola (alcoholic, macerate, aqueous without reserve time and infusion) in the control of Botrytis cinerea in vitro and in post-harvest of strawberries. Two experiments were conducted in vitro, being one to evaluate the mycelial growth and another the germination of conidia. The experimental design for the two experiments was completely randomized, in a 4 x 5 factorial scheme, and the modes of extraction of extracts and concentrations (0, 3, 6, 9 and 12 %), in 4 repetitions. In the trial mycelial growth, the experimental unit was a Petri dish, and a test tube in germination test of conidia. In post-harvest were tested four types of extracts at a concentration of 16 %. The experimental design was completely randomized, with 4 repetitions per treatment, being the plot composed by10 fruits/tray. The physico-chemical parameters evaluated were rotting, weight loss, firmness and titratable acidity. The biochemical analyzes were evaluated total proteins, anthocyanins and flavonoids, and the activity of the enzyme phenylalanine ammonia-lyase (PAL) and peroxidases. The results obtained allowed us to conclude that there was a reduction of mycelial growth and germination of conidia, as a function of the concentrations, but there were no differences between the extracts. The greater efficiency of extracts occurred at a concentration of 8.31 %, in evaluation with 96 hours. For germination, the behavior was decreasing linear, in other words, the increase of concentrations influenced the lower germination of conidia. The extracts: alcoholic, maceration and infusion reduced the rot caused by B. cinerea in post-harvest of strawberries. The extracts operate in fruits acidity modification, and in the behavior of peroxidases, but they had no effect on total soluble solids (TSS), pulp firmness, weight loss, anthocyanins, flavonoids,and activity of the PAL. The results obtained in this work, have demonstrate the potential of canola in the control of gray mold on post-harvest of strawberries, as well as the fungus Botrytis cinerea.